2006
DOI: 10.1007/s10577-006-1037-6
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of interphase chromosomes in postmitotic cells of the human brain by multicolour banding (MCB)

Abstract: Molecular cytogenetics offers the unique possibility of investigating numerical and structural chromosomal aberrations in interphase nuclei of somatic cells. Previous fluorescence in-situ hybridization (FISH) investigations gave hints of numerical chromosomal imbalances in the human brain, present as low-level mosaicism. However, as precise identification of aneuploidy rates in somatic tissues faces major difficulties due to the limitations of FISH using whole chromosome painting or centromeric probes, in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
87
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 13 publications
0
87
0
1
Order By: Relevance
“…However, our own multicolor banding (MCB) based studies [8] showed, that the chromosome shape is not lost in the interphase nucleus and one can even identify interphase chromosomes instead of only chromosome territory [9][10][11]. MCB is the only approach available at present that provides the possibility of characterizing the chromosomal integrity of arbitrary interphase cell populations [12,13]. It is still a matter of discussion what influences more the nuclear position of chromosomes: chromosome size or gene density.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our own multicolor banding (MCB) based studies [8] showed, that the chromosome shape is not lost in the interphase nucleus and one can even identify interphase chromosomes instead of only chromosome territory [9][10][11]. MCB is the only approach available at present that provides the possibility of characterizing the chromosomal integrity of arbitrary interphase cell populations [12,13]. It is still a matter of discussion what influences more the nuclear position of chromosomes: chromosome size or gene density.…”
Section: Introductionmentioning
confidence: 99%
“…It is still a matter of discussion what influences more the nuclear position of chromosomes: chromosome size or gene density. It has been repeatedly shown that small chromosomes preferentially locate close to the center of the nucleus, while large chromosomes can be found in the nuclear periphery of human fibroblasts [11][12][13][14][15]. Nonetheless, also evidence for a gene density-correlated radial arrangement of chromosomes in the nucleus was provided [16].…”
Section: Introductionmentioning
confidence: 99%
“…Its application allows the analysis of chromosome (chromosomal loci) positioning in interphase and chromosomal associations at "subchromosomal" resolution in a given nucleus (for more details see [4][5][6][7][8][9]). Evidently, analyzing each chromosomal region is likely to provide more reliable information in contrast to analyzing homogenously painted chromosomes or a single chromosomal region.…”
Section: Visualizing Interphase Chromosomesmentioning
confidence: 99%
“…To solve this problem, a technique providing for simultaneous visualization of the whole chromosome and its regions in a given nucleus has appeared to be required [3]. The development of interphase chromosome-specific multicolor banding (ICS-MCB) has led the way towards the high-resolution interphase cytogenetic analysis for Visualization of interphase chromosomes studying chromosomal numbers, structure and spatial arrangement within the nucleus [4][5][6][7]. Using ICS-MCB, chromosome architecture was evaluated in some tissues at "subchromosomal" resolution and specific positioning of chromosomal loci was shown to be linked to generation and behavior of rearranged chromosomes in interphase [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…ПослС роТдСния ΡƒΡ€ΠΎΠ²Π΅Π½ΡŒ CIN Π² ΠΊΠ»Π΅Ρ‚ΠΊΠ°Ρ… Π³ΠΎΠ»ΠΎΠ²Π½ΠΎΠ³ΠΎ ΠΌΠΎΠ·Π³Π° Π·Π½Π°Ρ‡ΠΈΡ‚Π΅Π»ΡŒΠ½ΠΎ сниТаСтся, ΠΏΠΎ-Π²ΠΈΠ΄ΠΈΠΌΠΎΠΌΡƒ, Π·Π° счСт Π·Π°ΠΏΡ€ΠΎΠ³Ρ€Π°ΠΌ-ΠΌΠΈΡ€ΠΎΠ²Π°Π½Π½ΠΎΠΉ смСрти Π°Π½ΠΎΠΌΠ°Π»ΡŒΠ½Ρ‹Ρ… ΠΊΠ»Π΅Ρ‚ΠΎΠΊ с хромосомными ΠΈ Π³Π΅Π½ΠΎΠΌΠ½Ρ‹ΠΌΠΈ Π½Π°Ρ€ΡƒΡˆΠ΅Π½ΠΈΡΠΌΠΈ. Π­Ρ‚ΠΎ ΠΏΡ€ΠΈΠ²ΠΎΠ΄ΠΈΡ‚, ΠΏΠΎ ΠΊΡ€Π°ΠΉΠ½Π΅ΠΉ ΠΌΠ΅Ρ€Π΅, ΠΊ Ρ‚Ρ€ΠΎΠΉΠ½ΠΎΠΌΡƒ ΡƒΠΌΠ΅Π½ΡŒΡˆΠ΅Π½ΠΈΡŽ уровня Π½Π΅ΡΡ‚Π°Π±ΠΈΠ»ΡŒΠ½ΠΎΡΡ‚ΠΈ (Π°Π½Π΅ΡƒΠΏΠ»ΠΎΠΈΠ΄ΠΈΠΈ) Π² ΠΊΠ»Π΅Ρ‚ΠΊΠ°Ρ… ЦНБ послС роТдСния [6,[9][10][11]. Однако, ΡΠΎΡ…Ρ€Π°Π½ΡΡΡΡŒ благодаря ошибкам ΠΏΡ€ΠΈ ΠΊΠ»Π΅Ρ‚ΠΎΡ‡Π½ΠΎΠΌ (митотичСском) Π΄Π΅Π»Π΅Π½ΠΈΠΈ ΠΈ ΠΏΠΎΡΠ»Π΅Π΄ΡƒΡŽΡ‰Π΅ΠΌ ΠΎΡ‚Π±ΠΎΡ€Π΅ Π½ΠΎΡ€ΠΌΠ°Π»ΡŒΠ½Ρ‹Ρ… ΠΈ ΠΏΠΎΡ€Π°ΠΆΠ΅Π½Π½Ρ‹Ρ… (Π°Π½Π΅ΡƒΠΏΠ»ΠΎΠΈΠ΄Π½Ρ‹Ρ…) ΠΊΠ»Π΅Ρ‚ΠΎΠΊ, такая Π½Π΅ΡΡ‚Π°Π±ΠΈΠ»ΡŒΠ½ΠΎΡΡ‚ΡŒ ΠΌΠΎΠΆΠ΅Ρ‚ Π΄Π°Ρ‚ΡŒ Π½Π°Ρ‡Π°Π»ΠΎ Ρ€Π°Π·Π»ΠΈΡ‡Π½Ρ‹ΠΌ ΠΏΠ°Ρ‚ΠΎΠ»ΠΎ-гичСским состояниям.…”
unclassified